Malaysian queer literature - Collin Jerome, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article examines Malaysian queer literature (MQL) in terms of what it is, its characteristic elements, and how the way it is written responds to the differential treatment of lesbian, gay, bisexual, transgender, and queer or questioning (LGBTQ) people in Malaysia. The article uses the secondary data analysis method to examine existing resources on MQL to ascertain what it is, its origin, and evolution. The article then applies the analytical method developed by Blackburn, Clark, and Nemeth to examine the elements of MQL in Malaysia’s anthologies of queer literature, namely, Body 2 Body - A Malaysian Queer Anthology (2009) and Mata Hati Kita/The Eyes of Our Hearts (2016). The analysis reveals that MQL is a new literary genre in the Malaysian literary scene and is produced for a number of reasons including to open up avenues of discussion about queer that remains subject to condemnation by the mainstream local society. Two characteristic elements of MQL are identified, namely, the multiple conceptions of sexual and gender identities, and the disruption of sexual and gender norms. The analysis also reveals that MQL is written with these elements in mind as a way to respond to the discriminatory treatment of LGBTQ people in the country. The article has implications for current efforts that seek to use MQL not only to provide readers with the diverse ways of being in the world but also to rethink existing discourses that continue to condemn LGBTQ people on the basis of gender and sexual diversity.